(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The study of the state of the adaptive immune system in polyp rhinosinusitis (PRS) remains relevant to this day, because the constantly changing ideas about the main processes of immune inflammation inevitably affect the current views on the pathogenesis of PRS. The etiology and pathogenesis of PRS remain unclear. Many works in this direction did not change the situation. However, ideas about the pathogenesis of PRS have recently undergone significant changes, primarily due to advances in the field of clinical immunology of ENT diseases. In all theoretical views on the genesis of nasal polyps, the involvement of the immune system, especially the immune status of the nasal mucosa, plays a leading role.